The military and the centenary of the independence of Peru in 1921 - Taype Castillo, Jaime Miguel (2021)
The ceremonies for the Centennial of the Independence of Peru that took place between the months of July and August 1921, were carried out with the collaboration of numerous institutions, which, led by the government of the day, achieved that the programmed acts reached levels of magnificence. However, the presence of the troops of our Army in the acts officiated for the occasion, consolidated the enhancement and showiness that every great event demands. The recommendations for the beautification of Lima, reception and accommodation of the foreign military detachments in the capital’s barracks, imposing parades, evolutions and retreats to the delight of the attendees, were the main actions by the Peruvian military that contributed to strengthening the image of our country internationally and restored self-esteem to Peruvians.